Dissecting the types and functions of religious humor in Nasreddin Hoja short-stories - Akmal, Saiful; Hamidi, Faraha; Ismed, Ikhramah; Nasir, Muhammad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Humor is a significant element in funny stories. This study aims to analyze the types and functions of humor in selected Nasreddin’s short stories from the book Nasreddin’s Funniest Stories (2011) by Yusup Priyasudiarja and Y. Sri Purwaningsih. By using the descriptive qualitative method, the study adopts textual analysis to examine the materials. Based on the analysis result, the types of humor applied in the stories are that joke, sarcasm, satire, replies to rhetorical question, clever replies, and double entendres. However, these writings lack some other typical types of spontaneous conversational humor used in short stories’ texts: puns and self-deprecation. Meanwhile, unintentional humor is also not found in the Nasreddin short stories because it is raised from the speaker’s misspellings, mispronunciations, errors in logic, and Freudian slips. Further reading shows that the underlying usage of humor in these stories is for social management: to control and mediate readers.